1990
DOI: 10.1136/pgmj.66.775.363
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ‘normal’ fluid retention in women and idiopathic oedema

Abstract: Summary:A sample of women attending a gynaecological outpatient clinic were examined for symptoms and objective signs of fluid retention. Patients completed a questionnaire on symptoms suggesting fluid retention and recorded daily weight and abdominal girth variation. Daily weight variation varied from 0-9 pounds (mode 2 pounds) with no discernable difference between premenstrual and intermenstrual variation. Daily girth variation varied from 0-6 inches (mode 1 inch). Symptoms of breast swelling were more comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…These changes may be considered an indirect measure of reduction in edema. Previous studies 35,36 conducted in patients with idiopathic edema have also used similar parameters for the assessment of edema.…”
Section: Discussionmentioning
confidence: 99%
“…These changes may be considered an indirect measure of reduction in edema. Previous studies 35,36 conducted in patients with idiopathic edema have also used similar parameters for the assessment of edema.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors demonstrated normal renal sodium excretion also in women with premenstrual syndrome and concluded that premenstrual symptoms are unrelated to sodium balance (Denning et al, 1990;Olson et al, 1996). Hussain et al found a significant fall of plasma ANP in the LP in women with premenstrual syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported no significant relationship between weight gain and symptomatic edema [29] and suggested that factors other than the degree of fluid retention may determine the incidence of this symptom [29]. Furthermore, the majority of women with IE has emotional liability and may also have lower thresholds for the perception of somatic sensations compared with women who are psychologically normal [1,29]. Our study also showed that the proportion of patients with symptomatic edema was higher in women, whereas VO was more commonly observed in men.…”
Section: Discussionmentioning
confidence: 99%